Dignity and grace : wisdom for caregivers and those living with dementia - Ramsey, Janet L. (Living with hope, 2018)
Whether a diagnosis of dementia--for you or for someone you are accompanying--arrives suddenly or gradually, this illness reorganizes a family's entire life. Drawing on her own experience, as well as interviews with eight family and professional caregivers, Janet L. Ramsey helps caregivers and those with impaired memories learn as they listen to each other. She also shows them how the Holy Spirit can awaken their imagination and understanding while they discover how to live with dementia.